Penerapan Six Sigma dalam Meningkatkan Kualitas Layanan Akademik - Zumroh Oktavia Harahap; Sohiron, Sohiron; Mohammad Yusuf (Lembaga Anotero Scientific Pekanbaru, 2025)
This research aims to examine the application of Six Sigma in improving the quality of academic services in educational institutions. The method used is a literature study, with the data collection stage which includes analysis of various references related to the implementation of Six Sigma in the academic sector. With this approach, it is hoped that it can provide a comprehensive understanding of the contribution of Six Sigma in creating more efficient and measurable service processes. The research results show that implementing Six Sigma can increase efficiency, reduce administrative problems, and meet student needs more effectively. A data-driven approach allows identifying appropriate solutions, such as updating academic information systems or improving coordination between staff, that have a positive impact on student satisfaction as well as the efficiency of the institution's work. The successful implementation of Six Sigma not only improves the quality of academic services but also strengthens the reputation of educational institutions. A more efficient process creates a more productive and quality academic environment, supports student development, and produces superior human resources who are ready to compete in the future.